REVIEW VIOLENCE AND THE EMPERORS IN LACTANTIUS Gianna Zipp, Gewalt in Laktanz' 'De mortibus persecutorum'. Millennium-Studien/ Millennium Studies, 95. Berlin: De Gruyter, 2021. Pp. xv + 298. Hardback, €113.95. ISBN 978-3-11-074066-0. Issue 16 (2022) - Gassman, Mattias
No abstract available